FEASIBILITY STUDY OF RICE KEBULI BUSINESS - Dibyantoro, Dibyantoro (Yayasan Education and Social Center, 2025)
The culinary business is experiencing rapid growth in the food and beverage sector. Today, the public is offered a wide variety of dishes designed to attract potential customers, creating greater profit opportunities for business owners. Dishes with distinctive characteristics provide uniqueness and can make a culinary establishment a special destination for consumers. One notable dish from the Middle East is nasi kebuli. Nasi kebuli is a blend of various spices that give it a unique and rich flavor, making it stand out among other dishes. This study aims to evaluate the feasibility of opening a nasi kebuli culinary business in Cilegon City, focusing solely on financial aspects. The analysis shows a Break Even Point (BEP) of IDR 29,840,729, a Return on Investment (ROI) of 17.79%, and a Payback Period (PP) of 5.6 months. Based on these results, the feasibility study concludes that this culinary business is viable and has promising profit potential while appealing to local consumers.